种线性振动电机 (2017)
本发明涉及种线性振动电机，所述线性振动电机包括具有收容空间的壳体、与所述壳体连接的弹簧件以及被所述弹簧件悬挂在所述容纳空间中的振子和线圈，所述振子设有第磁钢，所述线性振动电机还设有置于容纳空间中的与所述第磁钢相对的第二磁钢，所述第二磁钢固定在壳体上，所述线圈固定在振子上并且位于所述第磁钢和第二磁钢之间。由于线性振动电机中的线圈无需通过金属支架支撑，而是直接粘接在振子上，使得该种形式的磁路在保持高效率的同时，减少了线圈支架，还可降低了器件的成本，缩小了线性振动电机体积，同时减轻了线性振动电机的重量。 The invention relates to a linear vibration motor, which comprises a shell, a spring part, a vibrator and a coil, wherein the shell comprises an accommodating space; the spring part is connected with the shell; the vibrator and the coil are suspended in the accommodating space by the spring part; first magnetic steel is arranged on the vibrator; the linear vibration motor is also provided with second magnetic steel which is arranged in the accommodating space and is opposite to the first magnetic steel; the second magnetic steel is fixed on the shell; and the coil is fixed on the vibrator and is located between the first magnetic steel and the second magnetic steel. The coil in the linear vibration motor does not need to be supported through a metal bracket, and